2018
DOI: 10.1088/1755-1315/175/1/012221
|View full text |Cite
|
Sign up to set email alerts
|

Income of Seaweed Farming Households: A Case Study From Lemo of Indonesia

Abstract: Abstract. Seaweed farming is widely considered to be a profitable source of income and lucrative livelihood for coastal communities in Indonesia. This paper aims to analyze the income of seaweed farming households in the village of Lemo, Poleang Tenggara sub district, Bombana district, SE Sulawesi, Indonesia. This paper also assess perception of farmers and their participation in diversified livelihoods. A formal household survey was conducted using a structured questionnaire covering the patterns of income fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Graphing the various income estimates for seaweed farming against this household poverty line (Figure 3) indicates that, while seaweed farming income can bring families out of poverty, this is by no means always the case. Seaweed farming income in three reported studies, two in Southeast Sulawesi [51,61] and one in Rote Island [59], all fall below the poverty reference level (Figure 3). When considering rural poverty estimates, it is important to note that most farmers do not engage in seaweed processing as a full-time activity.…”
Section: Economic Benefits Are Variable But Generally Positivementioning
confidence: 92%
See 1 more Smart Citation
“…Graphing the various income estimates for seaweed farming against this household poverty line (Figure 3) indicates that, while seaweed farming income can bring families out of poverty, this is by no means always the case. Seaweed farming income in three reported studies, two in Southeast Sulawesi [51,61] and one in Rote Island [59], all fall below the poverty reference level (Figure 3). When considering rural poverty estimates, it is important to note that most farmers do not engage in seaweed processing as a full-time activity.…”
Section: Economic Benefits Are Variable But Generally Positivementioning
confidence: 92%
“…Reports of profitability for seaweed mariculture farms vary widely, from an average of IDR 10.6 million (USD 760) per annum in Southeast Sulawesi [51], from IDR 16.9 to 37.8 million (USD 1200-2700) per cycle across four districts in South Sulawesi [53], and from IDR 15.1 million (USD 1080) per annum for small seaweed farms (10 m × 25 m) up to IDR 29.9 million (USD 2135) per annum for large farms (10 m × 50 m) in Tual, Maluku [54]. A survey in Bombana District of Southeast Sulawesi found that the annual income from seaweed farming ranged from IDR 3.6 million (USD 257) to IDR 18.5 million (USD 1321), and that 92% of farmers earned an annual income between IDR 3.6 million (USD 257) and IDR 15.8 million (USD 1129) [61]. For reference, the September 2018 national rural poverty line in Indonesia was equivalent to IDR 4.7 million (USD 336) per annum per capita [62].…”
Section: Economic Benefits Are Variable But Generally Positivementioning
confidence: 99%
“…In Malaysia, governmental capacity building programmes have been set up to improve skills and knowledge among local seaweed cultivators, in particular women, in order stimulate rural community development (Kunjuraman et al 2019 ). Coastal and sustainable livelihood through seaweed mariculture has also been valued in Indonesia (Aslan et al 2018 ; Waters et al 2019 ). It should however be remarked that due to cultural differences in tradition for what kind of work men and women traditionally engage in, there are differences in the way family farming is done in different regions (Fig.…”
Section: Seaweeds and Livelihood In Developing Countriesmentioning
confidence: 99%
“…In 2017, Southeast (SE) Sulawesi was reported to produce up to 1,000,010 t that was mainly of red seaweed Kappaphycus alvarezii (Marine & Fisheries Agency of SE‐Sulawesi, 2014). This level of production is expected to increase in the future considering the potential of SE‐Sulawesi to extend seaweed farms across marine and coastal areas along its 1,740 km coastal line (Aslan et al., 2015, 2018).…”
Section: Figurementioning
confidence: 99%